IMPLEMENTASI KONTEN KREATIF @MAHARAGUNG. ORGANIZER DALAM MEMBANGUN BRAND AWARENESS - Bagus Purnomo Aji; Fitria Widiyani Roosinda; Julyanto Ekantoro (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
Brand Awareness does not appear on its own. Brand Awareness can be obtained by business owners with the creative content efforts it makes, with the development of advanced technology business owners are encouraged to develop and keep up with the rapid flow of technology. The potential of Instagram can be used as a medium to conduct Brand Awareness. This research aims to describe the implementation of creative content @maharagung.organizer in building Brand Awareness. It focuses on the use of social media instagram. In this study the authors used qualitative – descriptive methods. The author uses data in the form of interviews, observations and documentation. Mahar Agung Organizer is popular on Instagram because the Wedding organizer is located in Surabaya and his work is well known among young people who will carry out weddings and all affairs that require help from wedding organizers..